Assessment of the informativeness of serological methods for the diagnosis of infectious mononucleosis and seroepidemiological data on its prevalence - Dziubenko, Nataliia; Golubovska, Olga (ScienceRise: Medical Science, 2025)
The aim. To assess the prevalence of markers of the acute period of infectious mononucleosis (VCA IgM, VCA IgG, EBNA IgG, heterophilic antibodies in the monospot test and EBV DNA by PCR) based on the analysis of the Dila laboratory database in Kyiv during the three-year observation period (2022-2024), to investigate changes in diagnostic approaches in clinical practice, to determine the effectiveness of various laboratory methods in the context of differential diagnosis with SARS-like diseases and to develop optimized recommendations for the rational use of diagnostic resources. Materials and methods. A retrospective analysis of 64,812 laboratory tests performed during 2022-2024 in a single network of Kyiv laboratories was conducted. The analysis included serological tests for IgM antibodies to EBV capsid antigen, IgG to capsid antigen (VCA), IgG to nuclear antigen (EBNA), monospot test and EBV PCR. Statistical research methods. Results. The proportion of positive VCA IgM results remained stable throughout the three years of the study, fluctuating within 15.2-15.8%, which confirms the reliability of this marker of infectious mononucleosis. Serological indicators demonstrated high stability with low coefficients of variation - 4.3% for VCA IgM, 5.2% for VCA IgG and 6.5% for EBNA IgG. In contrast, EBV PCR revealed significant variability (coefficient of variation 118%) with a sharp decrease in positive results from 5.1% to 0.2%. A reorientation of the diagnostic practice of doctors from molecular to serological methods was also revealed - the proportion of serological tests increased from 65.5% to 71.4%, while molecular tests decreased from 34.5% to 28.6%. No seasonal fluctuations in the frequency of acute MI were detected (p=0.153), i.e. infectious mononucleosis was diagnosed equally throughout the year. Conclusions. VCA IgM should be used as the main marker for the diagnosis of the acute phase of MI. VCA IgG and EBNA IgG are important diagnostic elements for determining the stage of the infectious process. The use of PCR should be limited to cases with an atypical course of the disease or in clinically ambiguous situations